2004
DOI: 10.1111/j.1442-200x.2004.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for G71R mutation of the UGT1A1 gene in the Javanese‐Indonesian and Malay‐Malaysian populations

Abstract: The G71R mutation is present, but very rare, in Javanese-Indonesians and Malay-Malaysians. Thus, G71R mutation may not contribute to the high incidence of the neonatal jaundice in South-east Asian populations. DHPLC analysis is a very useful method for detecting the G71R mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…11 The 211G4A (G71R) was found at a frequency of 14.8% over the combined groups, which is consistent with the frequency of 13-23% found in other Asian populations. 10,12,13 The variant 686C4A was very rare in all the ethnic groups, with a frequency varying from 0.9 to 2.2%, similar to previous data. 10,11 Strong LD was found between the five polymorphisms but with lower r 2 values except for between À3156G4A and (TA)647 (r 2 ¼ 0.88) which is consistent with a recent study.…”
Section: Intra-ethnic Differences In Genetic Variantssupporting
confidence: 89%
“…11 The 211G4A (G71R) was found at a frequency of 14.8% over the combined groups, which is consistent with the frequency of 13-23% found in other Asian populations. 10,12,13 The variant 686C4A was very rare in all the ethnic groups, with a frequency varying from 0.9 to 2.2%, similar to previous data. 10,11 Strong LD was found between the five polymorphisms but with lower r 2 values except for between À3156G4A and (TA)647 (r 2 ¼ 0.88) which is consistent with a recent study.…”
Section: Intra-ethnic Differences In Genetic Variantssupporting
confidence: 89%
“…But some other studies reported no relationship between Gilbert syndrome and G6PD deficiency [5,9,14,15]; their findings were similar to the present study and no significant differences were observed between icteric and non-icteric neonates with regards to the Gilbert homozygoticity or hetrozygoticity.…”
Section: Methodssupporting
confidence: 80%
“…With regard to mutations in the coding region of UGT1A1, we previously reported that the c.211GϾA mutation is rare in Malays and Javanese (13,14). However, according to recent reports in the Chinese population in Malaysia and Singapore, the c.211GϾA mutation is observed more frequent than Malays and Javanese (26 -28).…”
Section: Discussionmentioning
confidence: 85%
“…Although several studies of the A(TA)7TAA and c.211GϾA mutations in the Southeast Asian population have been reported (13,14), the c.-3279TϾG and c.-3156GϾA mutations have never been examined in this population. Therefore, we determined the genotypes of the mutations, c.-3279TϾG, c.-3156GϾA, and A(TA)7TAA, in Malay infants with or without neonatal jaundice to evaluate the contribution of the mutations of the UGT1A1 promoter to the development of neonatal jaundice.…”
mentioning
confidence: 99%